Evaluation of a research hearing aid for audiological testing. - Andersen, Pernilla K.; Jürgensen, Lukas; Denk, Florian; Husstedt, Hendrik; Jürgens, Tim; Neher, Tobias (International Journal of Audiology, 2025)
Objective: Open-source hearing aid (HA) research tools provide avenues for testing new audiological concepts. This study compared a wearable research HA (RHA) – the "Portable Hearing Laboratory" – to a high-end commercial HA (CHA) in terms of aided outcome. Using this RHA, it also evaluated a fitting approach based on non-individualised gain presets. Design: Using a randomised repeated-measures design, participants completed speech recognition and speech quality assessments under unaided and several aided (RHA and CHA with omnidirectional and directional microphone settings) conditions. Furthermore, two approaches for prescribing amplification were evaluated with the RHA: (1) a preset approach based on non-verified clinical gain targets calculated for three standard audiograms, and (2) a best-practice approach based on individually prescribed and verified clinical gain targets. Study sample: Fifteen adults aged 50–78 years with symmetrical, mild-to-moderate sensorineural hearing losses. Results: The RHA and CHA gave similar audibility, speech recognition in quiet and in noise, and speech quality ratings in quiet and in noise. Relative to the best-practice approach, the preset approach resulted in less audibility but similar speech recognition in quiet and in noise. Conclusion: The RHA appears suited for testing new audiological concepts such as preset-based approaches to HA fitting.